Effectiveness of palivizumab immunoprophylaxis in infants with respiratory syncytial virus disease in Colombia - Juan Gabriel Piñeros; Jose De la Hoz-Valle; Clara Galvis; Astrid Celis; Oscar Ovalle; Carmen Cecilia Sandoval; Jaime Orrego; Saby Vides; Iader Rojas; Hernando Bustamante; Carlos Gallón; Jaime Alberto Mesa (Journal of Infection in Developing Countries)
Introduction: Respiratory syncytial virus (RSV) is one of the most important childhood infections. Objective: To evaluate the effectiveness and safety of palivizumab immunoprophylaxis in preterm infants at a high risk of severe respiratory syncytial virus infection during the RSV season in Colombia.